Genetic Mapping of APP and Amyloid-β Biology Modulation by Trisomy 21 - Mumford, Paige; Tosh, Justin; Anderle, Silvia; Gkanatsiou Wikberg, Eleni; Lau, Gloria; Noy, Sue; Cleverley, Karen; Saito, Takashi; Saido, Takaomi C.; Yu, Eugene; Brinkmalm, Gunnar; Portelius, Erik; et al. (The Journal of neuroscience, 2022)
Individuals who have Down syndrome (DS) frequently develop early onset Alzheimer's disease (AD), a neurodegenerative condition caused by the buildup of aggregated amyloid-β (Aβ) and tau proteins in the brain. Aβ is produced by amyloid precursor protein ( ), a gene located on chromosome 21. People who have DS have three copies of chromosome 21 and thus also an additional copy of ; this genetic change drives the early development of AD in these individuals. Here we use a combination of next-generation mouse models of DS (Tc1, Dp3Tyb, Dp(10)2Yey and Dp(17)3Yey) and a knockin mouse model of Aβ accumulation ( ) to determine how chromosome 21 genes, other than , modulate APP/Aβ in the brain when in three copies. Using both male and female mice, we demonstrate that three copies of other chromosome 21 genes are sufficient to partially ameliorate Aβ accumulation in the brain. We go on to identify a subregion of chromosome 21 that contains the gene(s) causing this decrease in Aβ accumulation and investigate the role of two lead candidate genes, and Thus, an additional copy of chromosome 21 genes, other than , can modulate APP/Aβ in the brain under physiological conditions. This work provides critical mechanistic insight into the development of disease and an explanation for the typically later age of onset of dementia in people who have AD in DS, compared with those who have familial AD caused by triplication of Trisomy of chromosome 21 is a commonly occurring genetic risk factor for early-onset Alzheimer's disease (AD), which has been previously attributed to people with Down syndrome having three copies of the amyloid precursor protein ( ) gene, which is encoded on chromosome 21. However, we have shown that an extra copy of other chromosome 21 genes modifies AD-like phenotypes independently of copy number (Wiseman et al., 2018; Tosh et al., 2021). Here, we use a mapping approach to narrow down the genetic cause of the modulation of pathology, demonstrating that gene(s) on chromosome 21 decrease Aβ accumulation in the brain, independently of alterations to full-length APP or C-terminal fragment abundance and that just 38 genes are sufficient to cause this.